DESIGNING OF HEXAGON SLOTTED MIMO ANTENNA FOR WIRELESS APPLICATION - Chouhan, Sanjay; Kushwah, Vivek Singh; Panda, Debendra Kumar (International Journal of Engineering Technologies and Management Research, 2018)
The wireless system capacity can be increased by the use of multiple antennas at transmitting and receiving side. The technology which uses multiple antennas called multiple inputs multiple outputs used to fulfils the demand of higher bit rate. In this paper two element antennas has designed using MIMO technique for dual band application and produced better isolation characteristics. In the proposed structure the high isolation was achieved using triangular and hexagonal cut structure. The presented simulated result produced low value of ECC and optimum value of VSWR in the given frequency band. The value of S12 is found less than -18 dB. The value of ECC is obtained 0.015 at 5.3 GHz. The proposed antenna operates in two frequency applications which are 3.59 GHz and 5.3 GHz.